3rd International Conference on Accounting, Business and Economics (ICABE) - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
“Global Opportunities and Challenges in Industry Revolution 4.0: Never Ending Innovation” More than 150 delegates from various countries including Australia, Malaysia & Indonesia AAGBS Representative - Dr Mohamad Nizam Jaafar & Dr Nurazree Mahmud